The theology of the book of Samuel - Goldingay, John (Old Testament theology, 2024)
"The Old Testament book of Samuel is an intriguing narrative that offers an account of the origin of the monarchy in Israel. This book explores the theological ideas in the narratives about Samuel, Saul, and David. This book uncovers key ideas about God's involvement in the lives of people, and their involvement with him through prayer and worship"--